1996
DOI: 10.1093/jmedent/33.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intraspecific Variation in Resistance to Desiccation by Adult Aedes (Stegomyia) spp. (Diptera: Culicidae) from Indonesia

Abstract: Desiccation survival times of adult mosquitoes were studied for yellow fever mosquito, Aedes aegypti (L.) (6 strains), Asian tiger mosquito, Ae. albopictus (Skuse) (5 strains), and Ae. paullusi Stone & Farmer (1 strain) colonized from South Sulawesi, Indonesia. At both 90 and 70% RH, Ae. aegypti males and females outlived the other species. The forest species Ae. paullusi was least resistant to desiccation. Strains of Ae. aegypti and Ae. albopictus from urban areas were more resistant to desiccation than consp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 0 publications
2
58
1
2
Order By: Relevance
“…Wesson, personal communication). Differential effects of climate on survivorship of eggs (e.g., Juliano et al 2002;Mogi 1992a,1992b), and adults (Mogi et al 1996) of these two species are well documented and probably account, in part, for coexistence in warmer, seasonally dry sites. Though various explanations have been proposed for the persistence of A. aegypti in urban environments (Juliano 1998), there have been no convincing experimental tests of hypotheses for variation along the urban-rural gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Wesson, personal communication). Differential effects of climate on survivorship of eggs (e.g., Juliano et al 2002;Mogi 1992a,1992b), and adults (Mogi et al 1996) of these two species are well documented and probably account, in part, for coexistence in warmer, seasonally dry sites. Though various explanations have been proposed for the persistence of A. aegypti in urban environments (Juliano 1998), there have been no convincing experimental tests of hypotheses for variation along the urban-rural gradient.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Larger also means higher energy reserves, 67 and by having a higher mass/surface area ratio, they might be less prone to desiccation than small mosquitoes. 69 These results suggest that the strategy of rearing large mosquitoes in the mass-releases of wMel-infected mosquitoes 1 may have contributed to the success of these releases. It is unclear if the large size of males also influences fitness in the field, although laboratory studies support the idea that larger males are fitter.…”
Section: Size and Shape In Released Mosquitoesmentioning
confidence: 92%
“…There are several prominent examples of local persistence of poorer competitors when they can tolerate more extreme physical conditions than can superior competitors (e.g., Connell 1961;Hemphill 1991) or cases where different physical environments yield different competitive outcomes (e.g., Dunson and Travis 1991;Warner et al 1993). Studies of A. albopictus and A. aegypti in Asia have demonstrated that these species differ in desiccation tolerances of adults and eggs, but also that there is pronounced geographic variation for both traits within both species (Sota and Mogi 1992a, b;Mogi et al 1996). Thus, there is a need to compare desiccation and temperature tolerances of A. albopictus and A. aegypti from Florida, and to determine if the pattern of local coexistence versus exclusion observed in the field in Florida can be accounted for by differences in desiccation or temperature tolerance.…”
Section: Introductionmentioning
confidence: 99%